1976
DOI: 10.1161/01.res.38.5.439
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between blood flow to ischemic regions and extent of myocardial infarction. Serial measurement of blood flow to ischemic regions in dogs.

Abstract: SUMMARY This study was designed to measure early sequential changes in blood flow to ischemic regions after acute coronary occlusion and to determine the relationship between blood flow and the extent of subsequent myocardial infarction. Initial studies were carried out on five dogs which verified using radioisotope-labeled microspheres, 7-10 pm in diameter, to measure changes in blood flow in small myocardial regions after acute coronary artery occlusions. Studies then were carried out on 11 awake dogs chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
56
2

Year Published

1977
1977
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(66 citation statements)
references
References 30 publications
8
56
2
Order By: Relevance
“…On the other hand, Schaper et al '7 and Bishop et al'0 found that epicardial flows increased only mildly, while flow to the endocardial core remained unchanged. As in our study, all these investigators9' 10,16 found that collateral flow measured a few minutes before the dogs were sacrificed was much higher than early postocclusion flow. Recently, an average 20% loss of radioactive microspheres has been found to occur differentially from necrotic myocardium beyond 24 hours after occlusion.…”
Section: Discussionsupporting
confidence: 80%
“…On the other hand, Schaper et al '7 and Bishop et al'0 found that epicardial flows increased only mildly, while flow to the endocardial core remained unchanged. As in our study, all these investigators9' 10,16 found that collateral flow measured a few minutes before the dogs were sacrificed was much higher than early postocclusion flow. Recently, an average 20% loss of radioactive microspheres has been found to occur differentially from necrotic myocardium beyond 24 hours after occlusion.…”
Section: Discussionsupporting
confidence: 80%
“…This degree of decreased collateral flow is quantitatively related to further decreases in regional left ventricular contraction24 25 and to further increases in myocardial infarction size. '19 [25][26][27][28][29] The mechanism of coronary steal when there are no stenoses proximal to the origin of the collaterals can be inferred to be the presence of some resistance in the large coronary arteries between the left main and the point of origin of the collaterals. Figure 4 intercepts the x-axis at -0.12 mm Hg ml-l*min, indicating that 12.5% of the total resting coronary vascular resistance value would have to be subtracted from the native coronary circulation between the left main and the origin of the collaterals to abolish the coronary steal.…”
Section: Discussionmentioning
confidence: 99%
“…The hearts were removed, the flowmeter probe and sonar crystals dissected free, and each heart fixed in 10% buffered formalin for at least 24 h. The atria, right ventricle, aorta, and large epicardial blood vessels were dissected from the left ventricle and discarded. The left ventricle was sectioned into four transverse rings as described (20). The rings were divided radially into six anatomic sections corresponding to the anterior papillary muscle, anterior free wall, septum, posterior free wall, posterior papillary muscle, and lateral free wall.…”
Section: Introductionmentioning
confidence: 99%